The light and fast organisation : a new way of dealing with uncertainty - Hollingworth, Patrick (Milton, Qld. : John Wiley and Sons Australia, Ltd, 2016)
Cut the organisational and operational dead weight to climb higher, faster The Light and Fast Organisation presents a blueprint for organisations looking to thrive in today's rapidly evolving business landscape. VUCA - Volatility, Uncertainty, Complexity and Ambiguity - has become the dominant mode of modern business, and leaders are overwhelmed. Competition and instability has increased while barriers to entry have fallen, chronic employee disengagement is on the rise and the global economic recovery is incredibly fragile; business leaders are uncomfortable, with threats to their business looming on all sides. This book proposes an alternative to the VUCA paradigm, one in which we learn to be comfortable with being uncomfortable, and a model for helping your organisation climb above the fray. Case studies from both business and mountaineering illustrate the benefits and practicalities of becoming light, fast, and agile and underscore the importance of self-awareness and self-reliance in minimising your exposure to risk. Business and mountaineering share many parallels, including frequent operation outside of the comfort zone. This book shows you the strong skills and effective strategies you need to reach the summit. * Get comfortable with discomfort * Adopt an 'Alpine Style' approach to business * Operate outside of the VUCA paradigm * Stretch outside your comfort zone to achieve more, faster Leaders must accept the current VUCA state and assess their preparedness, but it's possible to move beyond it by ingraining a 'light and fast' approach at the core of their organisations' values and operations. It's only through reaching beyond the 'safe' zone that we learn what we're made of, and build the foundations for successful leadership and teamwork. The Light and Fast Organisation is your practical coach for climbing the mountain, and your guide to the quickest route to the summit.
The perfect storm? -- The VUCA world -- The old world -- How we got so organised -- It's about people -- All that is wrong with expedition style -- All that is right with alpine style -- Making the transformation -- Three skills -- Three insights -- Three traits -- Pulling it all together.
Includes index.
Keywords: Leadership; Organizational change -- Management; Management; Success in business; Australian